Implementasi Sistem Informasi Pengelolaan Obat dan Barang Apotek Berbasis Web pada Apotek Sehati Demak - Indriyani, Sofiatul; Irawan, Yudie (Al-DYAS, 2026)
The management of medicines and supplies in pharmacies is a crucial aspect of ensuring the quality of health services; however, in many medium-scale pharmacies, including Apotek Sehati Demak pharmacy, inventory administration processes are still carried out manually, which can lead to recording errors, delays in reporting, and low operational efficiency. This study aimed to implement and evaluate a web-based drug management information system accompanied by an educational approach to improve the efficiency, accuracy, and transparency of pharmacy administration. An applied qualitative approach with a Participatory Action Research (PAR) model was used, involving stages of needs analysis, system design and development, implementation, user training, and ongoing accompaniment, with five pharmacy staff members selected purposively as participants. The system was developed using PHP and MySQL and includes features for recording incoming and outgoing drugs, stock management, monitoring expiration dates, and generating digital distribution invoices. The findings show an increase in the speed of administrative processes, a reduction in stock recording errors, decreased data duplication, and improved consistency and transparency in inventory reporting, while training and accompaniment were found to enhance users’ competence and readiness to adopt the system sustainably. The study concludes that the implementation of a web-based drug management information system using a participatory approach is effective in supporting the digitalization of administration in medium-scale pharmacies. The implications of this research affirm that the integration of system development with human resource capacity building is a key determinant of successful digital transformation in the health service sector.